Research on Optimal Layout Formation Techniques for Dynamic Planning of Single-Line Diagrams - Zhou, Hongyu; You, Feng; Wu, Qiang; Yang, Xiao; Bu, Xinlian (2023 International Conference on Computer Science and Automation Technology (CSAT), 2023)
A method based on dynamic programming algorithm to get the optimal layout solution to realize the generation of single-line diagram of regional power grid is proposed. A topological model is constructed based on the spatial data of the grid, a breadth-first algorithm is implemented to obtain multiple adjacency matrices and matrix traversal sequences that can form a connectivity map, and a square range that can accommodate all the equipments is computed based on the width of the adjacency matrices, and a mathematical model is established with the minimum spacing of equipments as the optimization objective. An algorithm for solving the optimal layout of dynamic programming is proposed, which is applied to solve the optimal layout array and finally orthogonalized according to the principle of least-crossing. The application example shows that the layout by the optimal solution is beautiful and efficient.